Image Processing Application: Assistance for Pandemic Online Learning - Haw, J. H.; Sari, Suhaila; Roslan, Hazli; Md. Taujuddin, Nik Shahidah Afifi; Ibrahim, N. (Multidisciplinary Applied Research and Innovation, 2021)
Mobile learning applications are playing a significant role during the COVID-19 pandemic. Especially during this pandemic time, students are compelled to continue their education through distance learning. Learning application will contribute to the learning process as it enables learning using the simulated environment that might increase the interest and understanding level of the users. In this study, an Image Processing application is developed to act as an educational tool,  which elevates students to a higher level of knowledge on basic principles of image processing. The development of the Android-based Image Processing learning application is implemented by using the Android Studio software. The Open Source Computer Vision (Open CV) library is added into the Android Studio as a library of programming functions for real-time image processing. This application provides the complete chapter based on the image processing course syllabus as well as the real-time processing functions. The notes provided in this application included 7 chapters which cover related digital image processing theories. The image processing techniques available are based on the notes provided. There are 10 sample images provided for users to perform image processing. Users are also able to retrieve images from their device’s gallery or capture images using the device’s camera. Then, the users can apply desired image processing techniques provided to the selected image depending on the users’ needs. The survey is conducted to analyze the performance of applications. In conclusion, the Image Processing application is developed and available for download in the Google Play Store. In addition, the results of the evaluation are encouraging and showed that the application has the potential to improve students’ knowledge of image processing.